2019
DOI: 10.2169/internalmedicine.2909-19
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Serum Hepcidin-to-ferritin Ratio with Erythroferrone after Hepatitis C Virus Eradication Using Direct-acting Antiviral Agents

Abstract: Objective Hepcidin is a master iron regulator hormone produced by the liver, but precise mechanism underlying its involvement in iron overload in hepatitis C virus (HCV) infection remains unclear. We investigated the serum hepcidin levels against iron overload before and after HCV eradication. Methods We prospectively investigated the iron metabolism characteristics in 24 patients with HCV genotype 1b infection before and after treatment. We also assessed the serum erythroferrone (ERFE) levels to investigate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Similarly, GO enrichment analysis, many up and down-regulated genes may play a very key role in the progression of SARS-CoV-2 infection. Enriched genes such as IFNL4 [117], ZFP36 [118], CD274 [119], MIR21 [120], CYP1A1 [121], CMPK2 [122], C4A [123], SERPINE1 [124], CCRL2 [125], CD69 [126], FAH (fumarylacetoacetate hydrolase) [127], ERFE (erythroferrone) [128], SERINC5 [129], ADI1 [130], AP2M1 [131], PRIMPOL (primase and DNA directed polymerase) [132], BIRC5 [133] and TF (transferrin) [134] were responsible for the advancement of various viral infections, but these genes may be involved in the progression of SARS-CoV-2 infection. Enriched genes such as APOBEC3G [135], NLRC5 [136], PTX3 [137], FAP ( broblast activation protein alpha) [138] and CAT (catalase) [139] were linked with the development of in uenza viral infection, but these genes may be associated with progression of SARS-CoV-2 infection as well.…”
mentioning
confidence: 99%
“…Similarly, GO enrichment analysis, many up and down-regulated genes may play a very key role in the progression of SARS-CoV-2 infection. Enriched genes such as IFNL4 [117], ZFP36 [118], CD274 [119], MIR21 [120], CYP1A1 [121], CMPK2 [122], C4A [123], SERPINE1 [124], CCRL2 [125], CD69 [126], FAH (fumarylacetoacetate hydrolase) [127], ERFE (erythroferrone) [128], SERINC5 [129], ADI1 [130], AP2M1 [131], PRIMPOL (primase and DNA directed polymerase) [132], BIRC5 [133] and TF (transferrin) [134] were responsible for the advancement of various viral infections, but these genes may be involved in the progression of SARS-CoV-2 infection. Enriched genes such as APOBEC3G [135], NLRC5 [136], PTX3 [137], FAP ( broblast activation protein alpha) [138] and CAT (catalase) [139] were linked with the development of in uenza viral infection, but these genes may be associated with progression of SARS-CoV-2 infection as well.…”
mentioning
confidence: 99%
“…Similarly, GO enrichment analysis, many up and down regulated genes may play a very key role in progression of SARS-CoV-2 infection. Enriched genes such as IFNL4 [116], ZFP36 [117], CD274 [118], MIR21 [119], CYP1A1 [120], CMPK2 [121], C4A [122], SERPINE1 [123], CCRL2 [124], CD69 [125], FAH (fumarylacetoacetate hydrolase) [126], ERFE (erythroferrone) [127], SERINC5 [128], ADI1 [129], AP2M1 [130], PRIMPOL (primase and DNA directed polymerase) [131], BIRC5 [132] and TF (transferrin) [133] were responsible for advancement of various viral infections, but these genes may be involved in progression of SARS-CoV-2 infection. Enriched genes such as APOBEC3G [134], NLRC5 [135], PTX3 [136], FAP ( broblast activation protein alpha) [137] and CAT (catalase) [138] were linked with development of in uenza viral infection, but these genes may be associated with progression of SARS-CoV-2 infection.…”
Section: Roc Analysismentioning
confidence: 99%
“…The suppression of hepcidin by ERFE promotes iron absorption from the intestine, resulting in increased iron storage (4,5). We previously reported an improvement in iron dysmetabolism associated with the reduction in the ERFE levels after HCV eradication (6). However, another study showed a correlation between increased LDL-C levels and interleukin-28B gene polymorphism after HCV eradication (7).…”
Section: Introductionmentioning
confidence: 99%